ANALYZING CELEBRITY IMPACT ON TIKTOK ON CAMILLE BEAUTY'S PURCHASE INTENTION - Julia Lathifah Kurniasari; Sentot Basuki Prayitno (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
In recent years, the rapid growth of social media platforms like TikTok has changed how beauty brands market their products, especially to younger audiences. This study,